2013
DOI: 10.1001/jama.2013.282540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progenitor Cell Mobilization With Granulocyte-Macrophage Colony-Stimulating Factor in Patients With Peripheral Artery Disease

Abstract: IMPORTANCE Many patients with peripheral artery disease (PAD) have walking impairment despite therapy. Experimental studies in animals demonstrate improved perfusion in ischemic hind limb after mobilization of bone marrow progenitor cells (PCs), but whether this is effective in patients with PAD is unknown.OBJECTIVE To investigate whether therapy with granulocyte-macrophage colony-stimulating factor (GM-CSF) improves exercise capacity in patients with intermittent claudication. DESIGN, SETTING, AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
(11 reference statements)
0
35
1
Order By: Relevance
“…Based on these promising results, investigators have launched several Phase I and II studies to evaluate the safety and efficacy of stem cell therapies for the treatment of ischemic heart disease (Bolli et al, 2011; Hare et al, 2012; Heldman et al, 2014; Perin et al, 2012; Traverse et al, 2011; Traverse et al, 2012), peripheral vascular disease (Poole et al, 2013), spinal cord injury (Mothe and Tator, 2012), multiple sclerosis (Uccelli et al, 2011), and stroke (Bang et al, 2005; Kondziolka et al, 2005; Lee et al, 2010). While safety has been clearly demonstrated, efficacy remains more elusive (Clifford et al, 2012; Fadini et al, 2010).…”
Section: Defining Hurdles To Clinical Translation: Findings From Precmentioning
confidence: 99%
“…Based on these promising results, investigators have launched several Phase I and II studies to evaluate the safety and efficacy of stem cell therapies for the treatment of ischemic heart disease (Bolli et al, 2011; Hare et al, 2012; Heldman et al, 2014; Perin et al, 2012; Traverse et al, 2011; Traverse et al, 2012), peripheral vascular disease (Poole et al, 2013), spinal cord injury (Mothe and Tator, 2012), multiple sclerosis (Uccelli et al, 2011), and stroke (Bang et al, 2005; Kondziolka et al, 2005; Lee et al, 2010). While safety has been clearly demonstrated, efficacy remains more elusive (Clifford et al, 2012; Fadini et al, 2010).…”
Section: Defining Hurdles To Clinical Translation: Findings From Precmentioning
confidence: 99%
“…Most of these studies showed no benefits of the SPC mobilizing agents for improving outcomes in PAD. The largest randomized trial to test the ability of GM-CSF to improve walking performance in people with PAD showed no benefit for the primary outcome measure of improved treadmill walking performance 25 . The ongoing PROPEL trial will test the ability of GM-CSF combined with the ischemic stimulus of supervised treadmill exercise to improve walking performance in people with PAD 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor cell-directed therapies may offer a new target for cognitive impairment prevention. 32,33 …”
Section: Discussionmentioning
confidence: 99%